PERANCANGAN ERGONOMIS ARMREST PORTABEL PADA MOBIL BARANG UNTUK MENGURANGI KELELAHAN PENGEMUDI - Worangian, Hubert Benedict; Widodo, Lamto; Adianto (Universitas Tarumanagara, 2025)
Truck drivers often suffer from fatigue due to long-distance driving, potentially reducing performance and increasing accident risks. This study aims to design an ergonomic portable armrest to alleviate discomfort in the shoulder and arm areas. The methods used include interviews, questionnaires, Nordic Body Map (NBM), and Rapid Entire Body Assessment (REBA). NBM results showed that most drivers experienced shoulder pain, while REBA analysis indicated a high-risk posture that requires correction. An ergonomic armrest was designed to be adjustable, easy to install, and equipped with additional features such as storage space. A 3D model was created using Fusion360 and tested for functionality. The results demonstrate that this armrest effectively reduces strain on the driver’s shoulders and arms.